Removal of diclofenac potassium from wastewater using clay-micelle complex - Karaman, Rafik (2012)
The presence of an ionized carboxyl group in the widely used non-steroidal anti-inflammatory (NSAID) drug diclofenacpotassium results in a high mobility of diclofenac and in its low sorption under conditions of slow sand filtration or subsoilpassage. No diclofenac degradation was detected in pure water or sludge during one month. Tertiary treatments of wastewaterindicated that the effective removal of diclofenac was by reverse osmosis, but the removal by activated carbon was lesssatisfactory. This study presents an efficient method for the removal of diclofenac from water by micelle-clay compositesthat are positively charged, have a large surface area and include large hydrophobic domains. Adsorption of diclofenacin dispersion by charcoal and a composite micelle (otadecyltrimethylammonium [ODTMA] and clay [montmorillonite])was investigated. Analysis by the Langmuir isotherm revealed that charcoal had a somewhat larger number of adsorptionsites than the composite, but the latter had a significantly larger binding affinity for diclofenac. Filtration experiments on asolution containing 300 ppm diclofenac demonstrated poor removal by activated carbon, in contrast to very efficient removalby micelle-clay filters. In the latter case the weight of removed diclofenac exceeded half that of ODTMA in the filter.Filtration of diclofenac solutions at concentrations of 8 and 80 ppb yielded almost complete removal at flow rates of 30 and60 mL min-1. One kilogram of ODTMA in the micelle-clay filter has been estimated to remove more than 99% of diclofenacfrom a solution of 100 ppb during passage of more than 100 m3.